Plant Defense Stimulator Mediated Defense Activation Is Affected by Nitrate Fertilization and Developmental Stage in Arabidopsis thaliana - Verly, Camille; Djoman, Atsin Claude Roméo; Rigault, Martine; Giraud, Frédéric; Rajjou, Loïc; Saint-Macary, Marie-Emmanuelle; Dellagi, Alia (Frontiers in Plant Science, 2020)
Plant defense stimulators, used in crop protection, are an attractive option to reduce the use of conventional crop protection products and optimize biocontrol strategies. These products are able to activate plant defenses and thus limit infection by pathogens. However, the effectiveness of these plant defense stimulators remains erratic and is potentially dependent on many agronomic and environmental parameters still unknown or poorly controlled. The developmental stage of the plant as well as its fertilization, and essentially nitrogen nutrition, play major roles in defense establishment in the presence of pathogens or plant defense stimulators. The major nitrogen source used by plants is nitrate. In this study, we investigated the impact of Arabidopsis thaliana plant developmental stage and nitrate nutrition on its capacity to mount immune reactions in response to two plant defense stimulators triggering two major defense pathways, the salicylic acid and the jasmonic acid pathways. We show that optimal nitrate nutrition is needed for effective defense activation and protection against the pathogenic bacteria Dickeya dadantii and Pseudomonas syringae pv. tomato. Using an npr1 defense signaling mutant, we showed that nitrate dependent protection against D. dadantii requires a functional NPR1 gene. Our results indicate that the efficacy of plant defense stimulators is strongly affected by nitrate nutrition and the developmental stage. The nitrate dependent efficacy of plant defense stimulators is not only due to a metabolic effect but also invloves NPR1 mediated defense signaling. Plant defense stimulators may have opposite effects on plant resistance to a pathogen. Together, our results indicate that agronomic use of plant defense stimulators must be optimized according to nitrate fertilization and developmental stage.